(untitled) (The Research of Medical Science Review, 2025)
Background: The umbilical cord is the lifeline that connects the placenta to the fetus. Early cord clamping and cutting of the umbilical cord is widely practiced as part of the management of labor. New studies have suggested delayed cord clamping with its potential benefits of improved iron status, hemoglobin, reduced need for blood transfusion Objective: To compare the effect of early cord clamping versus delayed cord clamping in term of mean hematological parameters at 24 hours, 48 hours and 3 months of age. Study design: Randomized Controlled Trial. Setting: Department of Obstetrics and Department of Neonatology, PAEC General Hospital, Islamabad. Study Duration: 18-Sep-2020 to 17-Mar-2021. Patients and Methods: A total of 98 patients with full term pregnancy with 37 to 41 weeks of gestation were included in this study. Eligible mothers admitted in the maternity hospital were randomized just before delivery into Group-1 (Early cord clamping group) or Group-2 (Delayed cord clamping group) and their Hemoglobin measured. After delivery, umbilical cord was clamped and cut 2-3 cm distance from the umbilical stump either within 30 seconds after delivery or at 3 minutes depending on the group. At 24 and 48 hours of life 1 ml of venous sample was obtained from the baby for estimation of haemoglobin and hematocrit. On follow up at 3 months of age, haemoglobin, hematocrit and serum ferritin were estimated again. Results: Mean gestational age was 39.08±1.32 weeks in group I and 39.86±1.32 weeks in group II, p-value 0.006. There were 27 (55.10%) male babies in group I versus 29 (59.20%) male babies in group II, while there were 22 (44.90%) female babies in group I and 20 (40.80%) female babies in group II (p-value 0.68). Hematocrit and hemoglobin levels at 3 months were significantly higher in group II (p-value 0.01 and 0.01 respectively) Serum iron levels at 24 hours after birth and at 3 months were higher in group II (p-value 0.02 and <0.001 respectively). While serum ferritin levels at 24, 48 and at 3 months were higher in group II (p-value <0.001, <0.001 and <0.001 respectively). Conclusion: In full-term infants, DCC for at least 60 s improved hematocrit, hemoglobin, serum iron and serum ferritin levels after birth, without any harmful effects on infants and mothers. Thus, DCC could be considered the first step to reduce anemia in the first year of life, especially in settings with a high prevalence of iron deficiency anemia.